Characteristics of shade-grown coffee (Coffea arabica L.) in North of Latin America and brazil: a comparative analysis - Jaramillo-Botero, Catalina; Martinez, Herminia Emilia Prieto; Santos, Ricardo Henrique Silva (Coffee Science - ISSN 1984-3909, 2007)
Shade-grown coffee (Coffea arabica L.) allows production in regions subject to frost or water deficit, reduces production costs, helps on biodiversity maintenance and diversifies production. In Brazil, coffee production in these systems is controversial and there is a huge demand on technical information about this subject. Almost always favorable coments are made about experiences in other countries of the continent, but in effect there is a great variety of cropping systems, from traditional to technified shade crop. Great part of shade cropping systems in Brazil have similar characteristics to those on technical shade systems, with soils that need higher amounts of fertilizers in order to maintain similar yields to the traditional system. Trees of commercial interest are frequently used for intercropping in coffee plantations in Brazil, but leguminous tree species are used instead in North of Latin America. In spite of the good quality of some published papers, there is a lack of information in many important aspects like soils, plant spacing, fertilization and management practices. This difficults comparisons among regions and among shaded coffee production systems, and examples from other countries must be examined with caution.